Islamic Ecotheology and the Global Environmental Crisis: An Interdisciplinary Pilot Study to Support the SDGs in an Indonesian Madrasah - Yunus Hamdani; Siti Aisah; Ahmad Halid (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to analyse how Islamic ecotheology is operationalised as an interdisciplinary framework to respond to environmental crises while supporting the achievement of SDGs at the madrasah level. Theoretical framework: A theoretical framework based on Islamic ecotheology with the concepts of caliph, amanah, mizan, and prohibition of facades, which is integrated with the perspective of education and sustainable development to shape ecological ethics and practices. Literature review: Literature review shows that Islamic ecotheology has a strong and effective ethical foundation when integrated into school culture, curriculum, and institutional practices. However, empirical studies in the context of madrassas are still limited. Method: The research used a mixed-method pilot design with a case study at MA Ma'arif Ambulu, Jember. Data were collected through questionnaires, interviews, observations, and documentation, and then analysed descriptively and qualitatively. Results: Results show very high levels of theological understanding, environmental awareness, and support for ecological action, but implementation is still moderate. Ecological value already exists, but it has not been fully institutionalised. Key findings include the concept of trust, strong moral support, practices that are still partial, and the need for collaboration. Implications: Islamic ecotheology has the potential to support the SDGs, but it requires strengthening curricula, policies, habituation, and cross-stakeholder collaboration to make its implementation more effective. Novelty: This research offers an early empirical contribution with an interdisciplinary approach that connects Islamic ecotheology and the SDGs in the context of madrasas, as well as highlighting the gap between normative values and real practice.